Pengaruh Store Atmosphere Terhadap Minat Beli Di Common Space Coffee & Bar Batam - Therecia Chau; Rezki Rezki Alhamdi; Wahyudi Ilham; Natal Olotua Sipayung (CV. ITTC INDONESIA, 2025)
The growth number of coffee shops that have become part of the lifestyle of young generations has intensified competition in the food and beverage industry. This study aims to analyze the effect of Store Atmosphere on customers’ purchase intention at Common Space Coffee & Bar Batam. Data were collected through observation, questionnaires, and literature studies involving 100 respondents selected using the purposive sampling method. The study employed a quantitative approach with Structural Equation Modeling–Partial Least Square (SEM–PLS) analysis using SmartPLS 3.0 software, consisting of Outer Model and Inner Model testing. The results indicate that Store Atmosphere has a positive and significant effect on purchase intention, with a path coefficient value of 0.934 and an R² value of 0.872. This finding implies that the more pleasant and well-designed the atmosphere created in the coffee shop, the higher the customers’ purchase intention. Overall, the study highlights the importance of interior design, layout, lighting, aroma, and environmental comfort in shaping positive customer experiences that enhance purchase intention.